GRIA2/ENPP3 Regulates the Proliferation and Migration of Vascular Smooth Muscle Cells in the Restenosis Process Post-PTA in Lower Extremity Arteries - Zhou, Mi; Qi, Lixing; Gu, Yongquan (Frontiers in Physiology, 2021)
Restenosis is the main restriction on the long-term efficacy of percutaneous transluminal angioplasty (PTA) therapy for peripheral artery disease (PAD). Interventions to prevent restenosis are poor, and the exact mechanism is unclear. Here, we aimed to elucidate the role of GRIA2 in the restenosis process post-PTA in lower extremity arteries. We searched the differentially expressed genes (DEGs) between atherosclerotic and restenotic artery plaques in the Gene Expression Omnibus (GEO), and 5 DEGs were identified. Combined with Gene Ontology (GO) enrichment analysis, GRIA2 was significantly correlated with the restenosis process. Tissue samples were used to examine GRIA2 expression by immunofluorescence staining of atherosclerotic and restenotic artery plaques. The regulation of GRIA2 in vascular smooth muscle cells (VSMCs) was confirmed by lentiviral transfection. Overexpression of GRIA2 promoted the proliferation and migration of VSMCs. Using Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and protein-protein interaction (PPI) network, a strong connection between ENPP3 and GRIA2 was discovered. In vitro results showed that high expression of GRIA2 in VSMCs enhanced the expression of ENPP3, while downregulation of GRIA2 downregulated ENPP3. GRIA2 is highly differentially expressed in restenotic arterial plaques, promoting the proliferation and migration of VSMCs through upregulation of ENPP3. These discoveries will help us to obtain a better understanding of restenosis in lower extremity arteries.